Hepatitis A and B vaccine uptake and immunisation among men who have sex with men seeking PrEP: a substudy of the ANRS IPERGAY trial. (8th December 2022) - Le Turnier, Paul; Charreau, Isabelle; Gabassi, Audrey; Carette, Diane; Cotte, Laurent; Pialoux, Gilles; Tremblay, Cécile; Spire, Bruno; Chaix, Marie-Laure; Meyer, Laurence; Capitant, Catherine; Delaugerre, Constance; et al.
Abstract : Vaccination against hepatitis A virus (HAV) and hepatitis B virus (HBV) is recommended in men who have sex with men (MSM). We assessed HAV and HBV vaccine uptake in the non-immune participants and their immunisation during follow-up of the ANRS IPERGAY (Intervention Préventive de l'Exposition aux Risques avec et pour les Gays) pre-exposure prophylaxis (PrEP) trial. During the ANRS IPERGAY trial among MSM (NCT 01473472), vaccination against HAV and HBV was offered free of charge to all non-immune participants at baseline. We assessed anti-HAV IgGs and anti-hepatitis B surface (HBs) antibodies (Abs) at baseline, 1–3 months after each vaccine dose and on the last follow-up visit. Vaccination uptake and immunisation were analysed in non-immune participants with at least 6 months of follow-up after the 1st vaccine dose. A total of 427 MSM with a median age of 34.8 years were analysed. Median follow-up was 2.2 years (Q1–Q3, 1.6–2.9). Absence of anti-HAV IgG at baseline (50.4%, 215/427) was associated with younger age (p=0.0001). Among HAV non-immune participants, 96.1% (197/205) received one or more vaccine doses and 91.0% (172/189) received two vaccine doses. Among HBV non-immune participants, 97.6 % (81/83) received one or more vaccine doses and 78.4% (58/74) received three doses. On the last-visit sample, anti-HAV IgG and anti-HBs Abs were respectively detected in 94.8% (95% CI 90.0% to 97.7%) and 79.6% (95% CI 66.5% to 89.4%) of participants with complete vaccination and in 80.0% (95% CI 51.9% to 95.7%) and 40.0% (95% CI 16.3% to 67.7%) of participants with incomplete vaccination. Vaccine acceptability against HAV and HBV infections was very high in MSM starting PrEP. Immunisation was high in participants with a full vaccination scheme. Physicians must consider PrEP visits as major opportunities to propose and complete HAV and HBV vaccination in at-risk non-immune subjects.